Design of Information System for Poor Household Data Collection in Glumpang Tiga Subdistrict - Baizah, Zahratul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Managing Poor Household Data (RPM) remains a major challenge for local governments aiming to enhance social policies and improve community welfare. Traditional manual data collection methods often lead to inaccuracies, delays, and inefficiencies, which affect the effectiveness of social programs. This research focuses on designing an information system for RPM data collection in Glumpang Tiga Subdistrict. The system utilizes Microsoft Access for database management and Visual Basic for the user interface, replacing outdated manual methods. It simplifies data entry, searching, and report generation, thus improving workflow and decision-making. Key features include user authentication, a user-friendly interface, and real-time data access, which enhance administrative efficiency and support quicker, more accurate decisions. Transitioning to an automated system offers numerous benefits, including faster data processing and reduced errors. The system is expected to improve the targeting and timeliness of social assistance programs, aiding poverty reduction efforts. Additionally, the system can serve as a model for other regions facing similar data management challenges. By integrating technology, public services become more efficient, contributing to better governance and more effective poverty alleviation